2021
DOI: 10.1038/s41598-021-81667-w
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 overexpression in EBV-positive gastric cancer is caused by unique genomic or epigenomic mechanisms

Abstract: Epstein-Barr virus-positive gastric cancer [EBV (+) GC] is a distinct GC subtype with unique genetic and epigenetic aberrations. Here, we examined resected GC samples and publicly available microarray data and The Cancer Genome Atlas (TCGA) database to identify the mechanism underlying overexpression of PD-L1 in EBV (+) GC. We found that high levels of PD-L1 overexpression in EBV (+) GC were caused by focal amplification of CD274. By contrast, relatively high expression of PD-L1 in tumor tissue and infiltratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 32 publications
(63 reference statements)
1
29
0
Order By: Relevance
“…Recently, Ge and colleagues found that EBV-encoded circular RNA CircBART2.2 upregulated the expression of PD-L1 in NPC and further inhibited the T-cell function ( 36 ). In other malignancies with positive EBV infection, IFN-gamma mediated signaling pathways, EBV microRNA, somatic gene mutations, and epigenetic modifications were also reported to regulate PD-L1 expression ( 45 , 46 ). Therefore, PD-L1 may be an effective target for immunotherapy as well as a useful biomarker for predicting metastasis and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ge and colleagues found that EBV-encoded circular RNA CircBART2.2 upregulated the expression of PD-L1 in NPC and further inhibited the T-cell function ( 36 ). In other malignancies with positive EBV infection, IFN-gamma mediated signaling pathways, EBV microRNA, somatic gene mutations, and epigenetic modifications were also reported to regulate PD-L1 expression ( 45 , 46 ). Therefore, PD-L1 may be an effective target for immunotherapy as well as a useful biomarker for predicting metastasis and survival.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have demonstrated an overexpression of PD-L1 in EBV-positive GC. 55 , 63 Indeed, a combined analysis of 4 studies involving 1307 Japanese patients indicated a significant association between EBV positivity and PD-L1 expression ( p < .0001). 10 Similar findings have also been reported in studies from Japan.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with reports demonstrating an induction of PD-L1 upon EBV infection with an involvement of LMP1. 74 , 75 …”
Section: Discussionmentioning
confidence: 99%